Balancing and Unbalance Identifications of Multi-Support Shafts and Rotors - Walczyk, Z. (Engineering Transactions, 1979)
The paper presents the theoretical foundations of a method to eliminate the effects of induction forces originating from the unbalancing of multi-support flexible rotors or transmission shafts. The method provides an adequate control of the rotor or shaft mass distribution and it includes the technical viability to carry out changes in this mass distribution. Also, a proposal is given as to how unbalancing in rotor or transmission shafts can be identified.